2022
DOI: 10.52728/ijtc.v4i1.412
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Implementation of E-Invoice 3.0 and Taxable Person Compliance to Value Added Tax Revenue at KPP Pratama Pasar Rebo

Abstract: Compliance of Taxable Person (PKP) is a complicated problem related to the implementation of an e-invoice application, especially the knowledge and perceptions of those who consider that making electronic-based tax invoices is difficult to do. This study aims to determine and analyze the effect of the e-invoice 3.0 application and Taxable Person compliance on the increase in VAT revenues. To obtain the research sample, the author used a non-probability sampling technique with the convenience sampling method. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…In Indonesia, both the introduction of electronic invoices and taxpayer compliance have had a significant positive impact on VAT revenue. Further improvements in its service to taxpayers will improve compliance and increase tax revenue, which could impact VAT revenue (Irawati et al, 2022 ). In addition, South Korea’s trust significantly affects cooperative VAT compliance when the discount amount increases (Kim et al, 2022 ).…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Indonesia, both the introduction of electronic invoices and taxpayer compliance have had a significant positive impact on VAT revenue. Further improvements in its service to taxpayers will improve compliance and increase tax revenue, which could impact VAT revenue (Irawati et al, 2022 ). In addition, South Korea’s trust significantly affects cooperative VAT compliance when the discount amount increases (Kim et al, 2022 ).…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…In Indonesia, Irawati et al ( 2022 ) findings show that “e-invoice” employment and taxable personal obedience significantly positively impact VAT incomes. They recommend for Pasar-Rebo-Jakarta’s key tax office continue advancing its service in providing info and conducting campaigns related to issuing e-invoices to taxable individuals to improve compliance.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The findings revealed that a substantial rise in VAT (along with other unobserved factors in the investigation) had a significant positive/negative effect on the interindustry fluctuation in business financial indicators, and this was even more pronounced with the COVID-19 cataclysm. Irawati et al (2022) calculated and analyzed the impact of the e-invoice 3.0 implementation and chargeable individual conformity to VAT revenue expansion. The researchers used a non-probability sampling approach in conjunction with convenience sampling as the method to obtain the data collection sample.…”
Section: Other Economiesmentioning
confidence: 99%
“…Several scholars had researched digital transformation to improve taxpayer compliance (Hesami et al, 2023;Hidayat et al, 2024;Putri, 2019), such electronic invoices (Bellon et al, 2022;Fan et al, 2018;Harianto et al, 2020;Irawati et al, 2022;Suendra, 2023) used by taxpayers could improve their compliance in making tax payments and increase tax revenue. Likewise, the use of e-filing (Cahyani et al, 2021;Muslichah et al, 2023;Yilmaz et al, 2013) provided convenience for taxpayers in reporting annual tax returns because it was based on digital technology that could be accessed at any time.…”
Section: Introductionmentioning
confidence: 99%